Reproductive potential of Pagrus pagrus (Perciformes: Sparidae) in coastal waters of Buenos Aires Province (Argentina) and Uruguay (34º-39ºS) - Militelli, Maria Ines (2017)
The reproductive potential of red porgy in coastal waters of Buenos Aires Province (Argentina) and Uruguay (34º-39ºS) was studied by means of a macroscopic and histological analysis of the gonads. Length and age at first maturity were determined, and fecundity, spawning frequency and egg quality were estimated. The spawning season extended from spring through summer between October and January with a peak of spawning in December. Length and age at maturity for sexes combined was 24.5 cm TL and 1.54 years, respectively. Batch fecundity ranged from 6,974 (25 cm TL) to 110,725 (39 cm TL) hydrated oocytes and showed significant linear relationships with total length and ovary-free weight. Relative fecundity ranged from 16 to 172 oocytes per female gram (ovary free). Spawning frequency was 58.5% during January 2011, indicating that females spawned once every 1-2 days at the peak of the spawning season. The life history of red porgy in Argentina and Uruguay was characterized by a young age at first maturity and partial, almost daily, spawning in a bounded time period, a life history strategy that would facilitate population expansion or colonization of new areas, and high population recovery rates or growth (r).